The Leadership Style of School Principals and Its Influence on Teacher Work Motivation - Tiara Agustine; Andrew Kyaw (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Education is fundamentally an effort to transmit values and guide humanity toward meaningful living within a civilized society. This study examines the influence of principals’ leadership styles on teachers’ work motivation using a descriptive qualitative approach through observation, interviews, and documentation. The results show that the principal’s leadership style significantly affects teachers’ motivation: supportive, democratic, and communicative leadership enhances enthusiasm and commitment, while authoritarian or inconsistent styles lower morale and productivity. Thus, effective leadership plays a crucial role in fostering an active, conducive, and joyful learning environment, emphasizing the need for principals to apply collaborative and empathetic approaches to improve both teacher motivation and educational quality.